Proficiency-based progression training: an 'end to end' model for decreasing error applied to achievement of effective epidural analgesia during labour: a randomised control study. Issue 10 (15th October 2018) - Kallidaikurichi Srinivasan, Karthikeyan; Gallagher, Anthony; O'Brien, Niall; Sudir, Vinod; Barrett, Nick; O'Connor, Raymund; Holt, Francesca; Lee, Peter; O'Donnell, Brian; Shorten, George
Abstract : Background: Training procedural skills using proficiency-based progression (PBP) methodology has consistently resulted in error reduction. We hypothesised that implementation of metric-based PBP training and a valid assessment tool would decrease the failure rate of epidural analgesia during labour when compared to standard simulation-based training. Methods: Detailed, procedure-specific metrics for labour epidural catheter placement were developed based on carefully elicited expert input. Proficiency was defined using criteria derived from clinical performance of experienced practitioners. A PBP curriculum was developed to train medical personnel on these specific metrics and to eliminate errors in a simulation environment. Seventeen novice anaesthetic trainees were randomly allocated to undergo PBP training (Group P) or simulation only training (Group S). Following training, data from the first 10 labour epidurals performed by each participant were recorded. The primary outcome measure was epidural failure rate. Results: A total of 74 metrics were developed and validated. The inter-rater reliability (IRR) of the derived assessment tool was 0.88. Of 17 trainees recruited, eight were randomly allocated to group S and six to group P (three trainees did not complete the study). Data from 140 clinical procedures were collected. The incidence of epidural failure was reduced by 54% with PBP training (28.7% in Group S vs 13.3% in Group P, absolute risk reduction 15.4% with 95% CI 2% to 28.8%, p=0.04). Conclusion: Procedure-specific metrics developed for labour epidural catheter placement discriminated the performance of experts and novices with an IRR of 0.88. Proficiency-based progression training resulted in a lower incidence of epidural failure compared to simulation only training. Trial registration number: NCT02179879 . NCT02185079 ; Post-results.